Long‐Term Variability of Aerosol Optical Depth in the Tatra Mountain Region of Central Europe. Issue 6 (28th March 2019) - Markowicz, K. M.; Zawadzka, O.; Posyniak, M.; Uscka‐Kowalkowska, J.
Abstract: This paper presents the results of long‐term observations (1964–2010) of direct solar flux at two stations in the Tatra Mountains in Poland (Central Europe). The measurements obtained from a Linke‐Feussner actinometers are used to estimate broadband (0.29–2.9 μm) and wideband (0.53–0.63 μm) aerosol optical depth (BAOD and WAOD, respectively). Both BAOD and WAOD at Mount Kasprowy Wierch (1, 991 m a.s.l.) and in Zakopane (851 m a.s.l.) show similar annual cycles with peaks during spring and summer. Coincidence of actinometer observation at the top of the Tatra Mountains and in Zakopane valley allows determination of AOD in the column between 851 and 1, 991 m a.s.l. Annual variabilities of both BAOD and WAOD for this layer are similar to PM10 concentration measurements in Zakopane. Conversely, BAOD and WAOD obtained at both stations show opposing annual variability, which is consistent with the Aerosol Robotic Network and model results in Central Europe. Long‐term data show significant reduction of both BAOD and WAOD in Zakopane (−0.018 ± 0.003 and −0.023 ± 0.003, respectively, per decade) and lower reductions at Mt. Kasprowy Wierch (−0.005 ± 0.002 and −0.009 ± 0.002, respectively, per decade). Trends for BAOD and WAOD defined between 851 and 1, 991 m a.s.l. are the same (−0.013 ± 0.004 per decade), which corresponds to the reduction of WAOD and BAOD by about 60% between 1964 and 2010. Conversely, emission data for the Zakopane region obtained from Emissions Database for Global Atmospheric Research inventories shows reduction of SO2 by a factor of 3 and of NO x and PM10 by about 40% between 1988 and 2010. Key Points: Annual cycle AOD as well as long‐range trend varies with altitude in the Tatra Mountains AOD long‐range negative trend is significantly higher in the lower station than at the mountain top indicating reduction of human emission AOD defined between valley and mountain top shows positive correlation with monthly means PM10 concentration